2019
DOI: 10.1101/773945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Reproducibility in Urology Publications

Abstract: Take Home MessageMany components of transparency and reproducibility are lacking in urology publications, making study replication, at best, difficult.IntroductionReproducibility is essential for the integrity of scientific research. Reproducibility is measured by the ability of investigators to replicate the outcomes of an original publication by using the same materials and procedures.MethodsWe sampled 300 publications in the field of urology for assessment of multiple indicators of reproducibility, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 38 publications
3
9
1
Order By: Relevance
“…Specifically, we noted that only one of the 59 articles that declared data was available complied with our FAIR assessment. This observation, depending on how availability for reuse is defined, is unfortunately consistent with this body of research which has reported 50-100% reductions in availability following interrogation of sharing statements [15][16][17][18][19][20][21][22][23][24][25] ; with factors such as the lack of unique and permanent identifiers, meta-data and licensing terms being noted as major pitfalls. 30,47 Furthermore, while we also noted a strong relationship between mandatory data sharing policies and actual data availability, we unfortunately also observed similarly sub-optimal compliance with these policies too; a finding that has been noted by other studies both inside and outside of medicine.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Specifically, we noted that only one of the 59 articles that declared data was available complied with our FAIR assessment. This observation, depending on how availability for reuse is defined, is unfortunately consistent with this body of research which has reported 50-100% reductions in availability following interrogation of sharing statements [15][16][17][18][19][20][21][22][23][24][25] ; with factors such as the lack of unique and permanent identifiers, meta-data and licensing terms being noted as major pitfalls. 30,47 Furthermore, while we also noted a strong relationship between mandatory data sharing policies and actual data availability, we unfortunately also observed similarly sub-optimal compliance with these policies too; a finding that has been noted by other studies both inside and outside of medicine.…”
Section: Discussionsupporting
confidence: 77%
“…Rather our observations that 19% and 4% of cancer researchers declared data and code were publicly available respectively are consistent with several studies reporting low, but increasing, declaration rates ranging between 3-24% and 0-2% respectively over several medical disciplines between 2014-2018. [15][16][17][18][19][20][21][22][23][24][25] The increase of declarations over time -particularly data availability declarations -is likely due to the growing number of medical journals that are adopting stronger policies on data and code sharing, particularly those that are requiring the addition of availability statements. For example, we note that a quarter of the unique 235 journals analysed in our study had adopted a mandatory data sharing policy for some or all data, which is higher than a previous survey of medical journal editors in the previous year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are consistent with prior reports of reproducibility and transparency in the medical ,10,12,14 and surgical literature. 7,8,11 Table 5 presents a comparison of the current study's results juxtaposed with results obtained from similar methods across other surgical disciplines and associated comparison tests for multiple proportions. In terms of open access status, plastic surgery articles were much less available-11.3 percent of journals were available by means of open access-than articles from other disciplines.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are consistent with prior reports of reproducibility and transparency in the medical ,10,12,14 and surgical literature. 7,8,11…”
Section: Discussionmentioning
confidence: 99%